Automated Ground Vehicles Navigation with Genetic Algorithm - Alireza Rezaee (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Automated ground vehicles are being used increasingly in automation of factories for material transmitting or other missions. The navigation of these vehicles is a challenge as the configuration of the environment such as factory changes. The path-planning problem has been shown to be NP-hard, thus this problem is often solved using heuristic optimization methods such as genetic algorithms. In this paper a genetic algorithm for path planning of the mobile robots specifically automated ground vehicles with a basic knowledge about navigation area boundaries and configuration of obstacles. The goal in this paper is to travel the shortest path in minimal time while avoiding obstacles in a navigation environment. For this reason, an effective structure for genetic algorithm was implemented. http://dx.doi.org/10.11591/telkomnika.v12i9.6271